Efeitos da perda da função ovariana e do exercício de força agudo sobre expressão de genes associados à atrofia muscular induzida pela artrite reumatóide - FURLANETTO JUNIOR, Roberto (2016)
Objective: evaluate the effect of resistance exercise (RE) after loss of ovarian function (ovariectomy) on muscle mass of gastrocnemius and the mRNA levels of IGF-1, atrogin-1, MuRF-1, and myostatin in an experimental model of rheumatoid arthritis in rats. Methods: 36 female Wistar rats (9 weeks, 195.3 ± 17.4 grams) were randomly allocated into six groups: control (CT-Sham; n = 6); group with rheumatoid arthritis (RA; n = 6); group with rheumatoid arthritis subjected to RE (RAEX; n = 6); ovariectomy without rheumatoid arthritis (OV; n = 6); ovariectomy with rheumatoid arthritis (RAOV; n = 6); ovariectomy group with rheumatoid arthritis subjected to RE (RAOVEX; n = 6). The ovariectomy (OV and RAOV) or Sham (CT-Sham or RA) procedures were performed at the same time, fifteen days before the rheumatoid arthritis induction. The RA and RAOV groups were immunized and then were injected with Met-BSA in the tibiotarsal joint. After 15 days of intra-articular injections with Met-BSA the animals of groups RAEX and RAOVEX were subjected to the RE and after six hours from workout were euthanized. Results: The rheumatoid arthritis induced reduction in cross-sectional areas (CSA) of gastrocnemius muscle fibers. The RAOV group showed a lower CSA of gastrocnemius muscle fibers compared to RA and CT-Sham groups. Skeletal muscle IGF-1 and atrogin-1 mRNA was increased in arthritics and ovariectomized rats. The increased IGF-1 mRNA was higher in OV group than in the RA and RAOV groups, but the atrogin-1 level was higher in RAOV group when compared to other arthritic groups. Antrogin-1 mRNA was also increased in the gastrocnemius muscle of arthritic and ovariectomized rats. However, the increased atrogin-1 mRNA was higher in RAOV groups than in the RA and OV groups. Gastrocnemius muscle MuRF-1 mRNA was increased in the OV and RAOV groups, but not in the RA and Sham groups. However, the RAOV group showed higher MuRF-1 mRNA than the OV group. The increased atrogin-1 and MuRF-1 mRNA level was lower in RAOVEX group than RAOV group when compared to other groups. The myostatin gene expression was similar in all groups except to RAOVEX, which was lower when compared to other groups. Conclusion: Loss of ovarian function results in increased loss of skeletal muscle-related ubiquitin ligases (atrogin-1 and MuRF-1) in arthritic rats. However, the acute RE reduces the atrogin-1, MuRF-1 and myostatin mRNA levels in muscle of arthritic rats affected by loss of ovarian function.